Brechas en la educación superior en turismo en el Perú - Regalado Pezúa, Otto (2014)
The growth of tourism in the world and in particular in Peru has made of this area an emerging productive activity with a lot of potential for development. Tourism is an economic activity which encourages foreign currency exchange as well as new employment opportunities. The objective of this article is to know whether or not there exist any gap between the formative offer in this area and the requirements of the labour market related to it. The research was conducted in two parts. The first one makes a literature review from secondary sources which found out there are limited research for the Peruvian case. The second one is an exploratory qualitative research which conducted semi-structured interviews with 20 experts from the public, private and academic sectors. The analysis and interpretation of the interviews' discourses were made from a deconstructive approach. The study concludes in Peru there is in fact a gap between higher education in tourism and the requirements of the labour market related to it.